Special Subsection Afterword: ESP Research and Cognitive Neuroscience: Possibly Incompatible - But Methodologically Complementary - Acunzo, David (Journal of Scientific Exploration, 2023)
This commentary considers the fields of extrasensory perception (ESP) research and cognitive neuroscience, discussing points of conflict and domains where they may be complementary. ESP research challenges the assumption in cognitive neuroscience that the mind is the product of known physical processes in the brain. Cognitive neuroscience methods and tools applied to ESP research could benefit and bridge the gap between the two fields. Firstly, concurrently studying subjective experiences and neural activity during ESP tasks would allow us to better characterize subjective states typically associated with ESP. Secondly, similarities between mind-wandering and free-response ESP experimental designs allow us to speculate on the potential implication of the default-mode network during the percipient’s experience. Finally, tools developed in computational neurolinguistics and natural language processing may become valuable to automatize judging procedures in free-response ESP paradigms such as remote viewing. Despite potentially incompatible assumptions about the mind and the brain, ESP research can gain new insights from cognitive neuroscience methods and approaches and can contribute in its own way to the study of human subjective experiences and cognition.